Investigating effort-reward imbalance and work-family conflict in relation to morningness-eveningness and shift work - Willis, Thomas A.; O'Connor, Daryl B.; Smith, Lawrence (Work and stress, 2008)
The effort-reward imbalance model (ERI; Siegrist, 1996 ) has been found to be a strong predictor of both psychological and physiological outcomes. Morningness-eveningness (M-E) is believed to relate to shift workers' ease of adjustment to irregular working patterns. However, it has not been investigated in conjunction with the ERI model. The present study (1) explored whether M-E acts as a predictor of psychological adjustment to shift work, above and beyond the contribution of the ERI model and (2) examined whether the formulation of the ERI model may be overly complex. A sample of police employees (N=112) completed a baseline questionnaire that contained the ERI model and a measure of M-E. Two months later, participants completed measures of work-family conflict and burnout. Regression analyses demonstrated that ERI was a significant predictor of psychological adjustment to shift work. Moreover, and for the first time, M-E was found to make a unique contribution to the prediction of work-family conflict, such that evening types reported greater levels of maladjustment. However, it did not make a unique contribution to the prediction of burnout. The possibility that the ERI model is unnecessarily complex received partial support, with the ratio score only contributing additional variance in one of four regressions. The results indicate that adjustment to shift work and attendant effects on work-family conflict can be affected by an individual's morning-evening typology.